Examining the effects of mindfulness practice and trait mindfulness on gambling symptoms in women with gambling disorder: a feasibility study. Issue 1 (2nd January 2020) - van der Tempel, Jan; McDermott, Katelin; Niepage, Mark; Afifi, Tracie O.; McMain, Shelley; Jindani, Farah; Singer, Ian; Paniak, Isabel; Anwer, Sana; Menezes, Karen; Lobo, Daniela; Zack, Martin
ABSTRACT: Women with gambling disorder (GD) exhibit high comorbidity, late onset and rapid escalation of symptoms, and a tendency to gamble to cope with negative affect. Mindfulness-based interventions (MBIs) may be especially helpful to address these issues. This project investigated the feasibility and therapeutic potential of a 10-week group MBI in treatment-seeking women with GD ( n =  9). The sample exhibited high scores on multiple measures of dysfunction and risk for GD. MBI was associated with clinically and statistically significant decreases in the Yale-Brown Obsessive-Compulsive Scale for Pathological Gambling and a Gambling Craving Scale; decreased severity on the Beck Depression Inventory ( p <  .05), and more consistent attention to negative affective words on an emotional Stroop task ( p = .05). Childhood exposure to violence and paternal over-control were inter-correlated, and each predicted lower distress tolerance. A between-groups design, comparing MBI with a validated GD treatment, would reduce the burden of repeated testing and enable direct recruitment through a treatment service to better target treatment-seeking individuals and promote retention in future studies. These preliminary data support the feasibility and therapeutic potential of MBI for women with GD.